Url redirect links and its importance calculated using parallel programming to drastically reduced the execution time - Dande, Madhu; Subramanian Lakshmi Narayanan, Bala; Diwadi, Abhishek (International Journal of Engineering and Technology, 2018)
Web URL Redirect Utility validates the URL links and generates the reports with details like number of hops, status and its importance. URL Redirect Utility will help the development team to fix the issue as well do the profiling for the URL links. The Utility will find the performance bottlenecks of the url links with that can improve the performance of each web page. URL redirect Utility designed and developed using dotnet MVC framework with parallel programming approach. Considered test scenario with an 20000 number of URLs which will be validated less than 20 min(1,200,000 msec) by running the utility in parallel which traditionally(sequential) takes more than 28.45 hours (102,420,000 msec ) to complete the execution. Efficiency of the Utility execution is 100% and execution time has reduced to 98 to 99% effort.Â Â